FUNGSI KELUARGA UNTUK MENCEGAH KEHAMILAN PADA REMAJA - yuswandi, yuswandi; Budiman; Afdillah Acep, Ikhlas (Faculty of Health Science and Technology, University of Jenderal Achmad Yani, 2024)
Background: Data in Cimahi Utara Subdistrict, Cipageran Village, shows that out of 265 marriage cases found, 28% of them were married at the age of 15-19 years and were students. Teenage pregnancy has an impact on the health of adolescents and their babies. Optimizing family functions has good effectiveness for adolescent growth and development. Objective: to determine the relationship between family function and pregnancy prevention among teenagers in the North Cimahi District, Cipageran Village. Method: The research design was a correlation study with a total sample of 52 nurse respondents who worked in the Covid-19 isolation room using the accidental sampling technique. Collecting data using a questionnaire. Data were analysed by univariate and bivariate with Pearson product moment test. Results: 55 people (100%) were women, 29 people (52.7%) were <45 years old, 44 people (80%) had a high school education, and 26 people (47.3%) had self-employed jobs. A total of 29 people (52.7%) had dysfunctional family functions and 32 people (58.2%) had good pregnancy prevention. Chi-Square test results show that there is a relationship between family function and pregnancy prevention in adolescents with p value (0.001) < alpha value (0.05). Conclusion: functional family function can prevent pregnancy in teenagers.